An alternative splicing isoform of wheat TaYRG1 resistance protein activates immunity by interacting with dynamin-related proteins. (2nd June 2022) - Zhang, Lu; Liu, Yuanming; Wang, Qiaohui; Wang, Chao; Lv, Shikai; Wang, Yanzhen; Wang, Jianfeng; Wang, Yajuan; Yuan, Jing; Zhang, Hong; Kang, Zhensheng; Ji, Wanquan
Abstract : Expression of TaYRG1.6, a splicing variant of the wheat NB-ARC-LRR gene, triggers cell death and enhances disease resistance, and TaYRG1.6 interacts with a dynamin-related protein. Abstract: Wheat ( Triticum aestivum ) is a commercially important crop and its production is seriously threatened by the fungal pathogen Puccinia striiformis f. sp. tritici West ( Pst ). Resistance (R) genes are critical factors that facilitate plant immune responses. Here, we report a wheat R gene NB-ARC-LRR ortholog, TaYRG1, that is associated with distinct alternative splicing events in wheat infected by Pst . The native splice variant, TaYRG1.6, encodes internal-motif-deleted polypeptides with the same N- and C-termini as TaYRG1.1, resulting in gain of function. Transient expression of protein variants in Nicotiana benthamiana showed that the NB and ARC domains, and TaYRG1.6 (half LRR domain), stimulate robust elicitor-independent cell death based on a signal peptide, although the activity was negatively modulated by the CC and complete LRR domains. Furthermore, molecular genetic analyses indicated that TaYRG1.6 enhanced resistance to Pst in wheat. Moreover, we provide multiple lines of evidence that TaYRG1.6 interacts with a dynamin-related protein, TaDrp1. Proteome profiling suggested that the TaYRG1.6-TaDrp1-DNM complex in the membrane trafficking systems may trigger cell death by mobilizing lipid and kinase signaling in the endocytosis pathway. Our findings reveal a unique mechanism by which TaYRG1 activates cell death and enhances disease resistance by reconfiguring protein structure through alternative splicing.